Evaluation of Bone Mineral Density in Subjects with Primary Hyperparathyroidism by Dual Energy X-Ray Absorptiometry - Haque, Rezwana; Hussain, Raihan; Begum, Shamim MF (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: Bone loss is a major complication of primary hyperparathyroidism (PHPT), and the extent of bone loss is an important factor for parathyroidectomy. Studies focused on this issue of bone loss in subjects with PHPT are quite rare in our country. This study will help the physicians to take proper action by giving an exact reflection of bone condition in subjects with PHPT. The purpose of this study was to evaluate the bone condition by measuring Bone Mineral Density (BMD), in subjects with PHPT using Dual Energy X-ray Absorptiometry (DEXA) and compare these findings with individuals without PHPT. Patients and Methods: It was an analytic cross sectional study (group comparison) carried out at National Institute of Nuclear Medicine and Allied Sciences (NINMAS) BSMMU campus, Dhaka from July 2015-December 2016. Subjects of PHPT diagnosed by biochemical evaluation (increased serum calcium and parathyroid hormone concentrations), between age ranges 15-45 years were selected as group-A. Individuals without biochemical evidence of PHPT or other major illness causing bone loss were selected as comparison group or as group-B. The subjects underwent BMD test by DEXA at lumbar spines from L1-L4 vertebra and the left femoral neck using Norland XR-46 densitometer. BMD was classified according to WHO criteria. Data presented on categorical form were analyzed using chi-squared test. While the data presented on continuous scale were analyzed using student’s t-test. In each analysis, level of significance was 5% and P value <0.05 was considered significant. Data were processed and analyzed with the help of computer software SPSS, version 20. Results: Total number of 90 subjects were selected for this study, 45 subjects with PHPT were in group-A and equal number of subjects without PHPT were in group-B. The findings derived from data analysis showed, a significantly more male participants in group-A. The mean age of group-A and group-B was 37.24 ± 8.03 years and 38.20 ± 5.74 years respectively. Mean BMI of group-A was 25.10 ± 4.35 kg/m2 in compare to 29.43 ± 5.17 kg/m2 in group-B. Higher BMI was noted in both groups. PHPT subjects with high BMI had low BMD. BMD expressed in absolute value (gm/cm2) and T score. BMD was significantly low in group-A (with PHPT) than in group-B (without PHPT), (p<0.0001). In group-A, prevalence of low BMD was 62.2% (osteopenia 37.8% and osteoporosis 24.4%) at lumbar spine and 84.5% (osteopenia 35.6% and osteoporosis 48.9%) at femoral neck. PHPT subjects had significant difference in both T score and BMD between lumbar spine and femoral neck. Conclusion: Primary hyperparathyroidism (PHPT) is shown to be associated with significantly reduced BMD especially at femoral neck. Thus, an increased fracture risk should consider if it is left untreated. Bangladesh J. Nuclear Med. 20(2): 129-135, July 2017